Effect of working memory load on electrophysiological markers of visuospatial orienting in a spatial cueing task simulating a traffic situation. (2nd November 2015) - Vossen, Alexandra Y.; Ross, Veerle; Jongen, Ellen M. M.; Ruiter, Robert A. C.; Smulders, Fren T. Y.
Abstract: Visuospatial attentional orienting has typically been studied in abstract tasks with low ecological validity. However, real‐life tasks such as driving require allocation of working memory (WM) resources to several subtasks over and above orienting in a complex sensory environment. The aims of this study were twofold: firstly, to establish whether electrophysiological signatures of attentional orienting commonly observed under simplified task conditions generalize to a more naturalistic task situation with realistic‐looking stimuli, and, secondly, to assess how these signatures are affected by increased WM load under such conditions. Sixteen healthy participants performed a dual task consisting of a spatial cueing paradigm and a concurrent verbal memory task that simulated aspects of an actual traffic situation. Behaviorally, we observed a load‐induced detriment of sensitivity to targets. In the EEG, we replicated orienting‐related alpha lateralization, the lateralized ERPs ADAN, EDAN, and LDAP, and the P1‐N1 attention effect. When WM load was high (i.e., WM resources were reduced), lateralization of oscillatory activity in the lower alpha band was delayed. In the ERPs, we found that ADAN was also delayed, while EDAN was absent. Later ERP correlates were unaffected by load. Our results show that the findings in highly controlled artificial tasks can be generalized to spatial orienting in ecologically more valid tasks, and further suggest that the initiation of spatial orienting is delayed when WM demands of an unrelated secondary task are high.